Integrative Medicine and Health Training for Thai General Practitioners (GP): A SEM Analysis - Bancha Daengneam; Samart Deebhijarn; Amnuay Saengnoree (Journal of Higher Education Theory and Practice, 2023)
The study aimed to determine which factors affected a Thai general practitioner’s (GP) intent to take integrative medicine and health (IMH) training. From the literature review, it was noted that IMH has other similar programs globally with names such as complementary and alternative medicine (CAM) and complementary and integrative medical procedures (CIM). Additionally, three latent variables were selected for the study and used in the confirmatory factor analysis (CFA) and structural equation model (SEM) LISREL 9.10 path analysis of the five hypotheses. The SEM results for each GP’s training attendance intention (TAI) discovered that first in importance was each medical professional’s learning ability (LA), then their perception of the innovative training course (ITC), and finally, their innovative attitude (IA). Final determination was then made that all the causal variables in the model had a positive influence on TAI, with the variability of factors influencing TAI (R2) at 41%. The three causal variables determined to affect TAI had total effect values of 0.64 (LA), 0.52 (ITC), and 0.43 (IA), respectively.
Keywords: Complementary and Alternative Medicine Studies; Patient Satisfaction in Healthcare